Community Participation in Mangrove Forest Management in Ekas Buana Village, Jerowaru District, East Lombok Regency - Muhammad Aminuddin; Anny Zuliyana (Journal of Multidisciplinary Science, 2025)
This research aims to see the level of participation of the Ekas Buana Village community in managing mangrove forests. This research is qualitative descriptive research. Data collection was carried out by giving questionnaires to respondents and interviews with resource persons as well as direct observation. Determining respondents used a purposive sampling approach by paying attention to the respondent's background. The results of this research show that the level of participation of the Ekas Buana Village community in managing mangrove forests varies, depending on the type of participation carried out. Participation in the form of providing input and ideas in managing mangrove forests is relatively high, while participation in the form of money or goods is very small or low.